Bede's Temple - O'Brien, Conor (Oxford Univ. Press, 2015)
Studying Bede's temple – Bede's temple in its intellectual context – Bede's temple as history – Bede's temple as cosmos – Bede's temple as the body of Christ – Bede's temple as church – Bede's temple as individual – Building Bede's temple
Literaturverz. S. [207]-235
Keywords: Bede; Synagogues; Temples